Pengabdian Kepada Masyarakat Melalui Kegiatan Melalui Kegiatan Pelatihan Bola Voli di SD Negeri 1 Sanguwatang - Syarif, Ahmad; Setiyawan, Sandi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
The Universitas Ma’arif Nahdlatul Ulama Kebumen Community Service Program is a tangible manifestation of students' academic obligations under the guidance of lecturers. Through community service activities in Sanguwatang Village, there is direct interaction between students and the community as a form of community service. One of the work programs carried out in Sanguwatang Village was a volleyball training activity for students of Sanguwatang 1 Public Elementary School, which aimed to contribute to increasing students' interest and skills in sports from an early age.This volleyball training was carried out on a scheduled basis and involved students from grade 6. The training material covered an introduction to basic techniques such as serving, passing, smashing, and teamwork exercises through mini games. The activity took place on the school field and was enthusiastically received by the students and teachers. Through this activity, it is hoped that students can develop their physical potential, strengthen their character through sportsmanship, and make sports a part of a healthy lifestyle. The training also serves as an interactive learning platform between students and teachers in an educational and enjoyable atmosphere.